2021
DOI: 10.1021/acsami.1c17408
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Apparently Inconspicuous but Sensitive Impacts on the Rollover Failure of Lithium-Ion Batteries at a High Voltage

Abstract: Layered oxides, such as Li­[Ni0.5Co0.2Mn0.3]­O2 (NCM523), are promising cathode materials for operation at a high voltage, i.e., high-energy lithium-ion batteries. The instability-reasoned transition metal dissolution remains a major challenge, which initiates electrode cross-talk, alteration of the solid electrolyte interphase, and enhanced Li-metal dendrite formation at the graphite anode, consequently leading to rollover failure. In this work, relevant impacts on this failure mechanism are highlighted. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…b) Suppression strategies on material level. Apart from cathode as the initiator, [48,50] particularly the design of electrolytes is an effective strategy aiming at TM scavenging, for example via Li x PO y F z species. [28,49] ChemElectroChem ("EC-free" electrolyte; Sigma-Aldrich, purity: battery grade), (iii) 1 m LiPF 6 in EMC + 1.0 wt% of LiDFP (American Elements; CAS No.…”
Section: Cell Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…b) Suppression strategies on material level. Apart from cathode as the initiator, [48,50] particularly the design of electrolytes is an effective strategy aiming at TM scavenging, for example via Li x PO y F z species. [28,49] ChemElectroChem ("EC-free" electrolyte; Sigma-Aldrich, purity: battery grade), (iii) 1 m LiPF 6 in EMC + 1.0 wt% of LiDFP (American Elements; CAS No.…”
Section: Cell Assemblymentioning
confidence: 99%
“…Even when electrode crosstalk is present, enhanced homogeneity of TM deposition at the anode surface can be also beneficial in terms of a more homogeneous SEI alteration, as it can prevent the detrimental TM‐ and HSAL “island‐like” accumulations, thus minimize the risk of short‐circuits and rollover failure. For example, this can be achieved via a more homogeneous SEI, e. g. with the support of vinylene carbonate (VC) additive, [28] a homogenous separator, e. g. fiber separators, or a higher anode porosity through control of electrode processing [48,57] …”
Section: Introductionmentioning
confidence: 99%
“…These knees were classified as resistance "pseudo-knees" due to increased electrolyte oxidation on the positive electrode, as evidenced by the strong dependence of the knee severity on discharge rate as well as positive electrode impedance measurements. For electrode design, Ma et al 6 and Klein et al 146 found that positive electrode particle coatings and low positive electrode loadings delayed the knee. Ma et al 6 and Glazier et al 147 also found that the graphite type (i.e., natural or artificial) can substantially impact the knee location; while natural graphite has larger irreversible expansion and thus higher parasitic reaction rates 147 , the root cause of the knee in this case is unclear.…”
Section: Cell Designmentioning
confidence: 99%
“…Rate-independent plating can occur if the ratio of negative electrode loading to positive electrode loading is too low (i.e., n:p < 1); 47 however, rate-dependent lithium plating can occur at low loading ratios if the negative electrode is too thick or the porosity is too low. 19,128,146 Additionally, small changes in the electrolyte can play an outsized role on the lifetime performance. Ma et al 6 demonstrated the sensitivity of the knee location to the electrolyte additive mixture; specifically, high methyl acetate (MA) concentrations (MA is used to increase electrolyte transport capability) and low LiPF 6 concentrations consistently led to earlier knees.…”
Section: Cell Designmentioning
confidence: 99%
See 1 more Smart Citation